A conditional-SGT-VaR approach with alternative GARCH models - Bali, Turan G.; Theodossiou, Panayiotis (My University, 2007)
This paper proposes a conditional technique for the estimation of VaR and expected shortfall measures based on the skewed generalized t (SGT) distribution. The estimation of the conditional mean and conditional variance of returns is based on ten popular variations of the GARCH model. The results indicate that the TS-GARCH and EGARCH models have the best overall performance. The remaining GARCH specifications, except in a few cases, produce acceptable results. An unconditional SGT-VaR performs well on an in-sample evaluation and fails the tests on an out-of-sample evaluation. The latter indicates the need to incorporate time-varying mean and volatility estimates in the computation of VaR and expected shortfall measures. © 2006 Springer Science+Business Media, LLC.
Keywords: Conditional value at risk; Expected shortfall; GARCH models; Skewed generalized t distribution